PENGEMBANGAN PERANGKAT LUNAK SIMULASI DINAMIKA KENDARAAN DENGAN REALITAS MAYA - Mochamad Safarudin; Joga Setiawan (Sekolah Tinggi Teknologi Mandala Bandung, 2016)
This paper presents an alternative approach in vehicle dynamics study which has been designed and developed using virtual reality simulation. Vehicle dynamics is usually visualized using graphical representation of vehicle attitude. In this paper, virtual reality simulation was developed to make clearer visualization of vehicle dynamics behaviors. An 8 degree of freedom vehicle dynamics, power train, automatic transmission and tire were modeled, while computer simulation and animation in a virtual reality environment were built. Several vehicle maneuvers can be simulated and vehicle parameters can be selected. In the simulation, both transient and steady state behavior can be visualized. Rather than using graphical representation, this approach can be more interesting to study vehicle dynamics. Besides providing vehicle dynamics study, the simulation can make additional excitement during learning process.